ANALYSIS OF INTEGRATED VILLAGE PLANNING TOWARDS INDEPENDENT VILLAGE IN KECAMATAN CILELES, LEBAK BANTEN DISTRICTN - Alfida Aziz; Faisal Marzuki; Mahendro Sumardjo (Econosains Jurnal Online Ekonomi dan Pendidikan, 2020)
This research was conducted to participate in advancing the Cileles Lebak Banten District, the purpose of this study was to identify the problems faced by the Cileles, Banten District to become an Independent Village so that a concrete picture would be obtained about the extent of the obstacles to being able to get to an independent village, members of the population. From the research was the Village Heads in Cileles, Lebak Banten District. This research uses qualitative analysis methods. Three villages that have been able to make plans to become independent villages, the research sample is 12 villages in the Cileles sub-district using surveys and questionnaires using Google Form. Keywords: Planning, Integrated village, Independent village